A systematic review of combined student‐ and parent‐based programs to prevent alcohol and other drug use among adolescents. (23rd March 2017) - Newton, Nicola C.; Champion, Katrina E.; Slade, Tim; Chapman, Cath; Stapinski, Lexine; Koning, Ina; Tonks, Zoe; Teesson, Maree
Abstract: Issues. Alcohol and other drug use among adolescents is a serious concern, and effective prevention is critical. Research indicates that expanding school‐based prevention programs to include parenting components could increase prevention outcomes. This paper aims to identify and describe existing combined student‐ and parent‐based programs for the prevention of alcohol and other drug use to evaluate the efficacy of existing programs.Approach. The PsycINFO, Medline, Central Register of Controlled trials and Cochrane databases were searched in April 2015 and additional articles were obtained from reference lists. Studies were included if they evaluated a combined universal intervention for students (aged 11–18 years old) and their parents designed to prevent alcohol and/or other drug use, and were delivered in a school‐based setting. Risk of bias was assessed by two independent reviewers. Because of the heterogeneity of the included studies, it was not possible to conduct a meta‐analysis and a qualitative description of the studies was provided.Key Findings. From a total of 1654 screened papers, 22 research papers met inclusion criteria, which included 13 trials of 10 programs. Of these, nine programs demonstrated significant intervention effects in terms of delaying or reducing adolescent alcohol and/or other drug use in at least one trial.Conclusion. This is the first review of combined student‐ and parent‐based interventions to prevent and reduce alcohol and other drug use. Whilst existing combined student‐ and parent‐based programs have shown promising results, key gaps in the literature have been identified and are discussed in the context of the development of future prevention programs. [Newton NC, Champion KE, Slade T, Chapman C, Stapinski L, Koning I, Tonks Z, Teesson M. A systematic review of combined student‐ and parent‐based programs to prevent alcohol and other drug use among adolescents. Drug Alcohol Rev 2017;36:337‐351]